Unravelling cumulative effects of human pressures on demersal fish traits using a driver-pressure-state-impact framework - Jennifer Rehren; W. Nikolaus Probst; Casper Kraan; Hermann Neumann; Shubham Krishna; Matthias Hasenbein; Serra Örey; Kim Ludwig; Kai W. Wirtz; Carsten Lemmen; Antje Gimpel; Vanessa Stelzenmüller (Marine Environmental Research, 2026)

Conservation potential of offshore windfarms for epibenthic invertebrates and fish communities in a heavily used regional sea - W. Nikolaus Probst; Jennifer Rehren; Casper Kraan; Holger Haslob; Hermann Neumann; Carsten Lemmen; Shubham Krishna; Maren Kruse; Kai Wirtz; Vanessa Stelzenmüller (Biological Conservation, 2026)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Thresholds of seascape fauna composition along gradients of human pressures and natural conditions to inform marine spatial planning - Casper Kraan; Holger Haslob; Wolfgang N. Probst; Vanessa Stelzenmüller; Jennifer Rehren; Hermann Neumann (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

Aquifer community structure in dependence of lithostratigraphy in groundwater reservoirs - Andrea Beyer; Michael Rzanny; Aileen Weist; Silke Möller; Katja Burow; Falko Gutmann; Stefan Neumann; Julia Lindner; Steffen Müsse; Hanka Brangsch; Jennifer Stoiber-Lipp; Martin Lonschinski; et al. (Environmental Science and Pollution Research, 2015)

Biodegradation potential of cyano-based ionic liquid anions in a culture of Cupriavidus spp. and their in vitro enzymatic hydrolysis by nitrile hydratase - Jennifer Neumann; Magdalena Pawlik; Dieter Bryniok; Jorg Thöming; Stefan Stolte (Environmental Science and Pollution Research, 2014)

Detection of Bioactive Exometabolites Produced by the Filamentous Marine Cyanobacterium Geitlerinema sp. - Nelson H. Caicedo; Jolanta Kumirska; Jennifer Neumann; Stefan Stolte; Jorg Thöming (Marine Biotechnology, 2012)

Wie falten Membranproteine? — Schritt für Schritt!? - Jennifer Neumann; Noreen Klein; Dirk Schneider (BIOspektrum, 2012)

Mercury exposure and neurochemical impacts in bald eagles across several Great Lakes states - Jennifer Rutkiewicz; Dong-Ha Nam; Thomas Cooley; Kay Neumann; Irene Bueno Padilla; William Route; Sean Strom; Niladri Basu (Ecotoxicology, 2011)